Re-presenting the margins: revisiting the Scottish countryside in L. G. Gibbon’s Sunset Song - Dasthakur, Saurav (EAST WEST JOURNAL OF HUMANITIES, 2013)
In his The Politics of Modernism: Against the New Conformists Raymond Williams comments on the gradual institutionalisation of the dominant (Anglo-American) version of modernism and the cooption of its subversive possibilities by the capitalist market dynamics, which it at least in some forms tried to challenge, or bypass, in the initial phase of its emergence in the late nineteenth-early twentieth century (Politics 35). As several critics have amply demonstrated, one of the deﬁning features of this ‘established,’ market-governed tradition of modernism was a many-pronged ideological ambivalence in its response to social modernity. Such ambivalence or inbetweenness of the modernists, which stands in conspicuous contrast to their aesthetic radicalism, as Williams has argued, was a part of the broader ‘structure of feeling’ of dominant cultural formations in their clash with emergent ones at a speciﬁc historical context. Hence Williams’ suggestion that artistic and other institutional practices, ‘these laws, constitutions, theories, ideologies, which are so often claimed as natural, or as having universal validity or signiﬁcance, simply have to be seen as expressing and ratifying the domination of a particular class’ (Problems 36-37). The dominant modernist discourses, more often than not, either prioritized the middle classes over the working classes, the masculine over the feminine, the urban over the provincial, the elite over the popular, or took an ambivalent stance in times of conﬂict between the two poles of these dyads. The crises the hegemonic class, gender or space faced at the turn of the century and the culture of negotiations, new compromises and new institutional practices the crises generated have been subjects of extensive critical enquiry in several disciplines. The historian Eric Hobsbawm, for one example, has devoted an entire chapter, ‘Who’s Who or the Uncertainties of the Bourgeoisie’ in his The Age of Empire 1875-1914 (165-91) to understand the nature of the culture of ambivalence which was one of the products of this crisis.